2022
DOI: 10.46306/lb.v3i3.180
|View full text |Cite
|
Sign up to set email alerts
|

Pembelajaran Berdiferensiasi Pada Pembelajaran Matematika Di Kurikulum Merdeka

Abstract: Mathematics learning should be carried out interactively, inspiring, challenging, motivating, fun, and meaningful, as well as accommodating the development of students' creativity, talents, and potential. Students can develop physically and psychologically according to their stages. This is in accordance with the concept of differentiated learning. Differentiated learning is an attempt to harmonize the learning process to meet the learning needs of each student. However, the implementation of differentiated le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
26

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 5 publications
2
27
0
26
Order By: Relevance
“…That is, PMM has an impact not only on teachers but also on students. The results of this study are supported by several studies stating that the use of PMM can improve teacher competencies and help the learning process (Aulia et al, 2023;Defa et al, 2023;Marisana et al, 2023;Ramdani et al, 2022;Suryadi & Hidayati, 2023), including in mathematics learning (Budiarti, 2022). These research findings are also supported by the results of (Susanti et al, 2023;Triscova et al, 2022), who reported that teachers found it helpful in understanding the implementation of the Merdeka curriculum and were highly inspired in designing teaching modules and creative learning content.…”
Section: Learning Implementation Results Below Standardsupporting
confidence: 81%
See 1 more Smart Citation
“…That is, PMM has an impact not only on teachers but also on students. The results of this study are supported by several studies stating that the use of PMM can improve teacher competencies and help the learning process (Aulia et al, 2023;Defa et al, 2023;Marisana et al, 2023;Ramdani et al, 2022;Suryadi & Hidayati, 2023), including in mathematics learning (Budiarti, 2022). These research findings are also supported by the results of (Susanti et al, 2023;Triscova et al, 2022), who reported that teachers found it helpful in understanding the implementation of the Merdeka curriculum and were highly inspired in designing teaching modules and creative learning content.…”
Section: Learning Implementation Results Below Standardsupporting
confidence: 81%
“…Their research did not discuss further and in detail the benefits obtained and the effectiveness of the innovations brought into the classroom. There was a study conducted by Budiarti (2022) that investigated how mathematics teachers utilized PMM. However, the study did not specify the benefits obtained, especially regarding the learning innovations' details.…”
Section: Introductionmentioning
confidence: 99%
“…Then a mapping of learning needs is carried out from the aspect of students' learning profiles with the aim of providing opportunities for students to be able to learn actively, efficiently and naturally. Factors that influence a person's learning include: environment, culture, visual, auditory and kinesthetic, so it is important for teachers to vary learning strategies and methods (Fitra, 2022;Gusteti, 2022;Faiz, 2022;Pratama, A., 2022).…”
Section: Figure 3 Elements Learningmentioning
confidence: 99%
“…Dalam matematika kompetensi ini mencakup pemahaman terhadap konsep-konsep matematika, kemampuan untuk memecahkan masalah matematika, keterampilan berhitung, serta kemampuan untuk menerapkan matematika dalam situasi sehari-hari dan dalam berbagai disiplin ilmu. Kompetensi memiliki hubungan yang erat dengan nilai hasil belajar siswa (Gusteti & Neviyarni, 2022) index by: untuk mengetahui kompetensi siswa dilihat dari nilai hasil belajar sebelum dan sesudah diberikan perlakuan. Dalam matematika semakin baik kompetensi seorang siswa, semakin baik mereka dapat mengerti dan menerapkan konsep-konsep tersebut dalam konteks pemecahan masalah (Kusumaningrum & Wijayanto, 2020).…”
Section: Metode Penelitianunclassified